Equipping library users with digital literacy skills as a solution to COVID-19 and other similar disasters: Lessons from Mzumbe University library users - Josephat, W.; Mosha, G.; Siyao, P. (Dar es Salaam University Press (DUP), 2024)
Proceedings of the 4th COTUL Scientific Conference, 7th-11th November, 2022